2
by veerpatilmyown2
Comment has been deleted

2014-11-29T19:21:38+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
5xy - 2xy - 11xy + 8xy

so as all the terms have same variable xy so we can simply do a algebraic summation

i.e. 5xy - 2xy - 11xy + 8xy  = 3xy - 3xy = 0
hope it helps
plz mark as best
2014-12-01T04:05:41+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
5 x y - 2 x y - 11  x y + 8 x y

= (5 - 2  - 11 + 8 ) x y
= (13  - 13) xy
= 0 * xy
= 0
===================
Formula is  :    a  x + b x = (a  + b) x
this is the distributive property in algebra

thanx n u r welcome veer